In vitro propagation of Rubus macrocarpus Benth. and Rubus bogotensis Kunth, as an ex situ conservation strategy (2017)
This research aimed to evaluate techniques for in vitro multiplication and rooting and ex vitro adaptation of wild blackberry plants (Rubus bogotensis Benth. and Rubus macrocarpus Kunth). In in vitro phases, the influence of culture media was evaluated based on Murashige and Skoog (MS) composition, with or without a 50% reduction in salts, vitamins, and myo-inositol and supplemented or not with benzylaminopurine (BAP), indole acetic acid (IAA), L-cysteine, agar, peat, perlite, and vermiculite. The ex vitro phase was based on a soil, rice husks, peat, and perlite substrate management. After two months of evaluation of the in vitro phases, it was determined that the MS medium at 50% salts, vitamins, and myo-inositol and supplemented with sucrose (15000 mg.l-1) and agar (5000 mg.l-1) was the most suitable for obtaining the highest values of apical length (cm), shoot number, rooting percentage, and root number. In ex vitro adaptation, the acclimation subphase, evaluated during three months, allowed to determine survival rates of 83.33% and 75% for R. macrocarpus and R. bogotensis, respectively. The average increase in stem length (cm) was 2.35 cm and 1.30 cm, respectively. In the greenhouse subphase, evaluated for four months, 100% plant survivorship was obtained, and 2.75 cm and 5.31 cm increases in average stem length (cm) for R. macrocarpus and R. bogotensis, were determined.